Women and Migration(s) II - Brooks, Kalia; Finley, Cheryl; Toscano, Ellyn; Willis, Deborah (Open Book Publishers, 2022)
Women and Migration(s) II draws together contributions from scholars and artists showcasing the breadth of intersectional experiences of migration, from diaspora to internal displacement. Building on conversations initiated in Women and Migration: Responses in Art and History, this edited volume features a range of written styles, from memoir to artists' statements to journalistic and critical essays. The collection shows how women's experiences of migration have been articulated through art, film, poetry and even food. This varied approach aims to aid understanding of the lived experiences of home, loss, family, belonging, isolation, borders and identity-issues salient both in experiences of migration and in the epochal times in which we find ourselves today. These are stories of trauma and fear, but also stories of the strength, perseverance, hope and even joy of women surviving their own moments of disorientation, disenfranchisement and dislocation. This collection engages with current issues in an effort to deepen understanding, encourage ongoing reflection and build a more just future. It will appeal to artists and scholars of the humanities, social sciences, and public policy, as well as general readers with an interest in women's experiences of migration.